The impact of training using the team game tournament method on anemia knowledge among youth red cross (PMR) members - Fadhila, Annisa Rahma; Wahyurin, Izka Sofiyya; Prasetyo, Teguh Jati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
Background: Anemia incidence in adolescents can be prevented by increasing the peers' knowledge through training and consumption of iron foods variety. The Youth Red Cross (PMR) is one of the elements in schools that can create peer tutors. The Team Game Tournament (TGT) is a cooperative learning method that encourages teamwork, healthy competition and develops respondents' communication skills.Objective: This study aimed to determine the effect of training using the Team Game Tournament on anemia knowledge in Youth Red Cross (PMR) members.  Materials and Methods: Quasi-experimental study with one group pre-test and post-test on 37 Youth Red Cross (PMR) members from senior high school using the Team Game Tournament. Conducted in July 2023. Knowledge variables were measured using a questionnaire and were analyzed using the Wilcoxon test.Results: Characteristics of respondents aged 15-16 years (64.9%), female (78.4%), and grade 10 (51.4%). Up to 55.0% were exposed to anemia education for ≥6 months by health center workers (45.0%). The Team Game Tournament affected respondents' knowledge (p<0.05). The percentage increase in knowledge is 3,68.Conclusion: There’s a difference in anemia knowledge of Youth Red Cross (PMR) members before and after peer tutor training using the Team Game Tournament.